Legal aspects of relations between the Crimean Khanate and the Ottoman Empire in views of European contemporaries. Pt. 1: Study of sources of 16th–17th cc. - Roman Pochekaev (Крымское историческое обозрение)
The problem of legal status of the Crimean Khanate towards the Ottoman Empire attracts substantial attention of scholars and stimulates lively discussions between adherents and opponents of idea on the vassalage of Crimea. To clarify the specific features of legal relations of the Crimean Khanate and the Ottoman Empire researchers use wide circle of historical sources, especially official documents and historical chronicles of Crimean and Ottoman origin as well as foreign diplomatic correspondence. This article is an attempt to characterize the legal aspects of relations between the Crimea and the Ottoman Porte on a base of works of European contemporaries–diplomats, travelers who visited the Crimean Khanate and the Ottoman Empire, historians and publicists. It seems, that the study of the “European view” on the format of Crimean-Ottoman relations could substantially supply ideas on the status of the Crimean Khanate towards the Ottoman dynasty which is presented in the modern historiography. Author uses notes of diplomats (Blaise de Vigenere, Daniel Printz, Reinhold Heidenstein, Marcin Bronevsky, Michalonis Lituani, Jacob Reutenfels, etc.), travelers, military officers, missionaries (John Smith, Emidio Dortelli d’Ascolli, Jiovanni da Lucca, William Levasseur de Beauplan, Pierre Chevalier, etc.), works of historians and publicists (Maciej from Mekhov, Alessandro Gwagnini, Maciej Stryjkowski, etc.). This is an analysis of such aspects as circumstances of establishment of Crimean dependence from Ottoman sultans, mutual rights and obligations of vassals and suzerains, specific features of international status of the Crimean Khanate, level of independence of its internal affairs. Special attention is paid to such controversial questions in the historiography as presence or absence of the “vassalage treaty” of the Crimean Khanate with the Ottoman Empire and agreement on possibility for Gerays to obtain the throne of the Ottoman Porte in case of the end of the Ottoman dynasty.